A Magnetometry Survey of the Second Augustan Legionary Fortress at Lake Farm, Dorset. (November 2020) - Stewart, Dave; Cheetham, Paul; Russell, Miles
ABSTRACT: A magnetometry survey of the Roman fort at Lake Farm, near Wimborne Minster in Dorset, first discovered in 1959, has upgraded the status of this site to a full legionary fortress: a major base of the legio II Augusta during the subjugation of the Durotriges and other tribes of south-west Britain. The interior layout of the fortress was identified for the first time, together with the original road and river connections, extensive areas of extramural activity and evidence for an earlier phase of the site as a marching camp.